Enhanced high energy density hybrid lithium ion capacitor by garnet ceramic electrolyte for lithium anode protection. (20th May 2020) - Zhan, Chenyang; Zhang, Kai; Li, Yaoting; Zhang, Ming; Shen, Zhongrong
Abstract: In this study, we report the fabrication of garnet-structure composited solid-state electrolyte with high compactness as a water-proof interlayer for multilayer water-proof protected-lithium-anode. It is revealed that with the addition of Li3 BO3 into the sintering precursor, the cubic phase garnet Li6.75 La3 Zr1.75 Nb0.25 O12 with high lithium ion conductivity and compactness can be achieved at a low temperature of 1000 °C with a "binder-like" Li3 BO3 glassy molten phase in the grain boundary, indicating Li3 BO3 plays an important role on the densification of grain boundary and the improvement of the relative density. 50 mol % Li6.75 La3 Zr1.75 Nb0.25 O12 –Li3 BO3 pellet shows a high lithium ion conductivity of 2.08 × 10 −4 S cm −1 and a good chemical stability in 21 m LiTFSI "water-in-salt" electrolyte at 25 °C. Hybrid lithium ion capacitor using this garnet-ceramic electrolyte as interlayer for water-proof protected-lithium-anode, 21 m LiTFSI electrolyte and commercial activated carbon as the cathode shows a high working voltage of 4.0 V and a high energy density of 228.9 Wh (kg-carbon) −1 at a power density of 1343.2 W (kg-carbon) −1 . Graphical abstract: Image 1 Highlights: Lithium ion capacitors consist by protected-lithium-anode and 21 m LiTFSI electrolyte. Garnet-type solid state electrolyte is used in high-voltage lithium ion capacitor. High concentration Li3 BO3 is used to densify Garnet-type electrolyte. Garnet-type electrolyte shows a good stability in 21 m LiTFSI.